ҲУҚУҚ ФАЛСАФАСИГА ДОИР ҚАРАШЛАР: НАЗАРИЯ ВА АМАЛИЁТ (Scientific journal of the Fergana State University, 2023)
This article reveals the concept and meaning of the philosophy of law in the system of legal branches.  The interrelation of the constituent elements of the philosophy of law, in particular between the legal culture, legal reason and other conventional components, is also comprehensively studied.